2019
DOI: 10.1038/s41467-019-09436-y
|View full text |Cite|
|
Sign up to set email alerts
|

Unifying scrambling, thermalization and entanglement through measurement of fidelity out-of-time-order correlators in the Dicke model

Abstract: Scrambling is the process by which information stored in local degrees of freedom spreads over the many-body degrees of freedom of a quantum system, becoming inaccessible to local probes and apparently lost. Scrambling and entanglement can reconcile seemingly unrelated behaviors including thermalization of isolated quantum systems and information loss in black holes. Here, we demonstrate that fidelity out-of-time-order correlators (FOTOCs) can elucidate connections between scrambling, entanglement, ergodicity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
198
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(216 citation statements)
references
References 69 publications
18
198
0
Order By: Relevance
“…This differs from the exponential growth rate of an OTOC, λ OTOC , which is rather the log of the phase space average of sensitivity squared. Since the log of the average is larger than the average of the log, we have [22][23][24][25][26][27][28]:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from the exponential growth rate of an OTOC, λ OTOC , which is rather the log of the phase space average of sensitivity squared. Since the log of the average is larger than the average of the log, we have [22][23][24][25][26][27][28]:…”
mentioning
confidence: 99%
“…Originally, it was conceived to describe N two-level atoms coupled to a single optical cavity mode. Several recent works [25,27,28] considered the OTOCs in this model. In the classical limit, its Hamiltonian H = 1 2 (q 2 + p 2 ) + x + γzq (A1) describes an SU (2) (pseudo)-spin (x, y, z) and a harmonic oscillator (p, q), interacting with a coupling constant γ > 0.…”
mentioning
confidence: 99%
“…The chaotic dynamics observed in the classical limit S → ∞ can be studied experimentally via the hallmark of sensitivity to perturbations. Recent theoretical and experimental work has shown that such sensitivity is accessible in quantum systems by measuring out-of-timeorder correlators (OTOCs) [1,34,[68][69][70][71][72][73], which quantify the spread of operators in time via the commutator C(t) = [V (t), W (0)] 2 . The connection to classical chaos is made clear in the semi-classical limit: for operators V = S z i , W = S z j , one can show that, to lowest order in a 1/S expansion, C(t) ∝ (∂S z i (t)/∂φ j ) 2 for a small rotation φ j at site j about the z-axis [74].…”
Section: Experimental Realitiesmentioning
confidence: 99%
“…A nice feature of the continuous protocol is that we obtain a total Hamiltonian that can be mapped to the original SDF-only Hamiltonian with an enhanced coupling strength. This can be useful for studies on spin-motion coupling [35]. Additionally, the gate time is not limited by the motional mode splitting and the enhancement is more advantageous for gT 30 as shown in Fig.…”
Section: Comparison To the Continuous Protocolmentioning
confidence: 99%